(untitled) - Aktion psychisch Kranke; Dachverband Gemeindepsychiatrie e.V.; Bundesverband der Angehörigen psychisch erkrankter Menschen (Psychosoziale Umschau, 2020)
Psychsoziale Umschau is the highest-circulation interdisciplinary psychiatric magazine in the German-speaking region. Since the early 80s, Psychosoziale Umschau serves its readers as a platform for discussions regarding the developments in social psychiatry. The Federal Association of Families of People with Mental Illness (BApK), the Dachverband Gemeindepsychiatrie e. V., and Aktion Psychisch Kranke (APK) use Psychosoziale Umschau as their nationwide bulletin. Additionally, every issue covers self-help topics for people with experiences of psychiatry. The magazine informs psychiatric staff, people with experiences of psychiatry, their loved ones, as well as volunteers. Topics of Psychosoziale Umschau: Social and health policy Managing mental illness Therapy and assistance services – especially on an outpatient basis Employment and rehabilitation